KAJIAN KAPASITAS MASYARAKAT DALAM PENGELOLAAN WISATA MINA PADUKUHAN BOKESAN DI KAWASAN MINAPOLITAN NGEMPLAK KABUPATEN SLEMAN - Azimah, Amalia; Damayanti, Maya (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2019)
Bokesan village is included in the minapolitan area which is set as a development area for mina tourism. The success of tourism management needs the capacity of the community to manage tourism activities. However, its capacity is still unknown, so there is a need to study the capacity of the existing community. The research  aims to assess the capacity of the community in managing tourism at Bokesan district in the Minapolitan area of Ngemplak region. The research method used was qualitative method.The results of the study show that the emergence of community capacity in tourism activities is influenced by economic and social motivation. The results of community capacity studies at the individual level indicate that the capacity of individuals who are able to support tourism activities in Bokesan district are the capacity of those in culinary, fishing spot, swimming pools owner  and tour guides. While the study of organizational capacity shows that the capacity of P2MKP Mina Ngremboko organization is stronger than the capacity of Bokesan POKDARWIS organization. It is influenced by the leadership factor of the chairman of the organization. In the P2MKP Mina Ngremboko, the chairman’s’ leadership was able to direct their subordinates to have good commitment and coordination in tourism management. Whereas in the POKDARWIS Bokesan, the chairman have not been able to direct the subordinates well, so that the commitment of members becomes weak.  The form of capacity building in Bokesan Village was carried out in the form of training, assistance, tourism facilities development, cooperation, recruitment, and participation in associations and communication forums.